PENTINGNYA ETIKA ISLAM PADA PROFESI AKUNTAN - Ivahzada Marella Edgina (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2023)
This study explores the extent to which accountants are involved in financial reporting scandals caused by the ethical judgment of certain accountants and a number of academics recommend that the education system be held accountable. The paper argues that in applying accounting ethics, especially Islam, accounting education must focus on ethical codes and religious values.